Imaginaries revolving around the Accounting Theory course: The case of the Public Accounting program of the Universidad de la Amazonía - Gómez Cano, Carlos Alberto; Sánchez Castillo, Verenice; García Capdevilla, Diana Ali; García Andrade, Lorena; Barrera Rojas, Yuri Alejandra (Cooperativismo & Desarrollo, 2017)
Introduction: A critical review about accounting education in Colombia, and the importance of accounting theory in the formation of public accountants is presented. This demonstrates the need to articulate ¡ members of the academic communities in order to foster disciplinary development.Methodology: The guiding paradigm was analytical empirical, and the research type was exploratory and descriptive, with survey application.Discussion and results: As a result, the research revealed the wrong interpretation of accounting theory, the shortcomings of teacher action and the apathy of future public accountants on this important issue for the construction of a solid accounting discipline. In addition, emphasis is made on the need for the program’s intervention in order to generate processes of academic transformation.Conclusions: Exhaustive reviews on the course of Accounting Theory, and how it articulates with other academic spaces must be done. This demands the intervention of all members of the university community.
Keywords: university community; education; imaginaries; accounting theory